Hubungan Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan (Studi Kasus PT. Wira Karya Jaya) - Dwi Yasmita; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research discusses the interaction between work motivation and job satisfaction on employee performance. Research results show that satisfied and motivated employees tend to demonstrate better attendance, high levels of commitment, reduce absenteeism, and increase overall contribution at work. The references used include various theories and concepts of human resource management. High work motivation can increase productivity and work quality, while job satisfaction can strengthen employee involvement and commitment. Positive interactions between motivation and job satisfaction can result in improved work quality and reduced employee absenteeism levels. PT. Wira Karya Jaya, a medical equipment distributor company, strives to create a work environment that supports employee physical well-being to increase work motivation and productivity. Abraham Maslow's hierarchy of needs and job satisfaction factors also play an important role in improving employee performance.